PITOT TUBE BLOCKAGE BY MUD-DAUBER WASP AS A MECHANISM OF A MOTION OF AN AIRCRAFT THROUGH MIRCE FUNCTIONABILITY FIELD - Knežević, Jezdimir (Journal of Applied Engineering Science, 2019)
MIRCE Mechanics is the discipline of MIRCE Science that focuses on the scientific understanding and description of the phenomena that govern the motion of functionable system types though the MIRCE Functionability field [1]. A full understanding of the mechanisms that generate the motion is essential for the accurate predictions of the functionability performance of functionable system types using MIRCE Science. According to the 2nd Axiom of MIRCE Science the motion of a functionable system type through MIRCE Space is a result of imposed natural phenomena or human activities, which are jointly called functionability actions. Thus, the main objective of this paper is to address pitot tube blockage by mud-dauber wasps as a mechanism that influences the motion of an aircraft through the MIRCE Functionability Field. Although it is not a frequent and globally realised phenomenon, it is a physically observable one, which is experienced by aircraft on the ground in areas where these types of insects are present. The paper also presents a set of a possible prevention and management actions regarding this specific phenomena.